EFEKTIVITAS PENGGUNAAN BAHASA ISYARAT DALAM PELAYANAN PELANGGAN DI COFFE SHOP OLEH KARYAWAN DENGAN PENYANDANG DISABILITAS TUNARUNGU - Stephanie Rosalind; Chontina Siahaan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2022)
Coffee shops today are very easy to find in many places. Even small towns we can find cafes or coffee shops. But deaf coffee shop coffee shop has a different concept from most other coffee shops. This coffee shop has the uniqueness of its service that uses sign language as a way of their interaction. All employees who work in this coffee shop are deaf or disabled. The shortcomings they have are precisely what they use as the potential of the business they are currently running. That's why the author became interested in doing research on this coffee shop. The purpose of this study was to show how the communication process between hearing friends and deaf friends and their effectiveness in interacting with each other in the buying and selling process. In addition, this research also aims to find out what marketing strategies and goals this coffee shop wants to achieve. The research methods used in this study are literature studies, interviews, and data collection by conducting surveys about deaf coffee shops.